Mechanism of Exogenous Silicon in Enhancing Cold Stress Tolerance in Solanum lycopersicum L. Seedlings: Insights from Resistance and Quality Indicators - Fan Zhang; Yihong Zhao; Yuanbo Zhang; Yu Shi; Leiping Hou; Abid Khan; Ruixing Zhang; Yi Zhang (Horticulturae)
Environmental stress, notably the exposure to low temperatures during the early developmental stages of seedlings, has been identified as a critical determinant impacting the yield and quality of tomato crops cultivated in greenhouses. Silicon (Si), recognized as a beneficial element, is posited to mitigate the adverse effects of such stress on plant physiology. This study explores whether exogenous Si fertilizer can effectively alleviate the stress of low temperature and cold damage on tomato plant growth, fruit yield, and quality. Tomato plants were placed under low temperature conditions (6 °C at night, daily average temperature 15 °C), with normal temperature conditions as the control (below 16 °C at night, daily average temperature 28 °C), and two different concentrations of nano Si and ionic Si (50 mg·L−1 and 200 mg·L−1) were sprayed on the leaves, with an equivalent amount of deionized water as the control, for a total of 10 treatments. Relevant indexes were measured to investigate the effects of exogenous Si on tomato resistance, yield, and quality under low-temperature stress. The results show that compared with the control treatment, the plant height, stem diameter, and fresh weight of above-ground and underground parts of tomato seedlings decreased significantly by 46.52%, 42.53%, 28.81%, and 28.97%, respectively, after 15 days of low-temperature stress (p < 0.05), and in order to resist low temperature, the activity of antioxidant enzymes and the content of osmotic adjustment substances were up-regulated in seedlings. Ultimately, low-temperature stress inhibited the morphological growth, nutritional quality, and yield of fruits. Both concentrations of Si application can promote the growth and biomass accumulation of tomato plants under low temperature conditions. Moreover, it significantly ameliorated the osmotic adjustment and antioxidant capacity of the plants, thereby alleviating the low-temperature stress. Under low-temperature stress, 50 mg L−1 ionic Si was the most effective for increasing tomato yield per plant, which was significantly increased by 22.44% compared with the control treatment (p < 0.05). Consequently, the study advocates for the application of 50 mg·L−1 ionic Si fertilizer as a strategy to mitigate the impact of low-temperature stress on tomato plants. Furthermore, the use of nano Si fertilizer has been demonstrated to exert a significant influence on enhancing both the yield and quality of tomatoes, with a 50 mg·L−1 concentration of nano Si fertilizer leading to a notable increase in yield by 20.15% under normal temperature conditions (p < 0.05). These findings are intended to furnish a theoretical foundation and practical direction for advancing research aimed at combating the detrimental effects of low-temperature stress in the context of protected vegetable cultivation.